International perspectives on consumers' access to justice - Rickett, C. E. F.; Telfer, Thomas G. W. (Cambridge University Press, 2003)
Consumer protection law in the age of globalisation poses new challenges for policy-makers. Leading scholars outline key problems faced in adopting consumer laws to the global marketplace. Topics include standard form contracts, the legal challenges posed by mass infection (such as CJD), consumers and services, and consumer bankruptcy law.